Driving Factors Behind Changes in Australia’s Immigration Policy (2008–2013): A Case Study of Operation Sovereign Borders - Alif, Nahda Salsabila (Dinasti Publisher, 2025)
The issue of asylum seekers and refugees has been a persistent challenge for Australia. Despite ratifying the 1951 Refugee Convention and actively participating in multilateral forums such as the Bali Process, Australia, under the Tony Abbott administration in 2013, implemented a controversial unilateral policy known as Operation Sovereign Borders (OSB). This policy emphasised a militaristic approach through